2020
DOI: 10.1111/echo.14757
|View full text |Cite
|
Sign up to set email alerts
|

Ortner’s syndrome due to large bilharzial pulmonary artery aneurysm

Abstract: Ortner's syndrome (cardiovocal syndrome) is a rare cause of unilateral vocal cord paralysis that results from compression of the left recurrent laryngeal nerve by enlarged vascular structures. Most commonly, it is caused by an enlarged left atrium, but other rare causes include ascending aortic aneurysm or pulmonary artery aneurysm. Although very rarely encountered nowadays, bilharziasis is still one of the main causes of pulmonary artery aneurysm in endemic areas. Hereby, we report a case of Ortner's syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Patients may also present with signs of advanced PH leading to right ventricular failure and systemic volume overload state such as weight gain, peripheral edema (e.g., ankle edema), ascites, and abdominal, jugular venous distention, hepatomegaly, hepatojugular reflex, and low-volume arterial pulses [26]. Pulmonary artery (PA) enlargement due to progressive PH may lead to physical manifestations comprising angina, i.e., chest pain on exertion, hoarseness of voice, cough, wheezing, lower respiratory tract infections, and atelectasis [30]. These symptoms manifest due to the compression of various anatomical structures by the enlarged PA, including the left main coronary artery (LMCA), left recurrent laryngeal nerve leading to Ortner Syndrome, and bronchi [13,30].…”
Section: Clinical Characteristics 41 History and Physical Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients may also present with signs of advanced PH leading to right ventricular failure and systemic volume overload state such as weight gain, peripheral edema (e.g., ankle edema), ascites, and abdominal, jugular venous distention, hepatomegaly, hepatojugular reflex, and low-volume arterial pulses [26]. Pulmonary artery (PA) enlargement due to progressive PH may lead to physical manifestations comprising angina, i.e., chest pain on exertion, hoarseness of voice, cough, wheezing, lower respiratory tract infections, and atelectasis [30]. These symptoms manifest due to the compression of various anatomical structures by the enlarged PA, including the left main coronary artery (LMCA), left recurrent laryngeal nerve leading to Ortner Syndrome, and bronchi [13,30].…”
Section: Clinical Characteristics 41 History and Physical Examinationmentioning
confidence: 99%
“…Pulmonary artery (PA) enlargement due to progressive PH may lead to physical manifestations comprising angina, i.e., chest pain on exertion, hoarseness of voice, cough, wheezing, lower respiratory tract infections, and atelectasis [30]. These symptoms manifest due to the compression of various anatomical structures by the enlarged PA, including the left main coronary artery (LMCA), left recurrent laryngeal nerve leading to Ortner Syndrome, and bronchi [13,30]. Patients may also present with clinical signs owning to underlying comorbidities such as arthralgias, skin rash, cough, history of thrombosis, and daytime sleepiness [13].…”
Section: Clinical Characteristics 41 History and Physical Examinationmentioning
confidence: 99%
“…When we analysed the age at which patients were diagnosed with an aneurysm, we observed that young patients can be affected. The youngest patient included in our review was 18-years old, and overall, five patients were below 40 years [ 13 , 18 , 19 , 22 , 27 ]. This differs from the usual age at diagnosis of atherosclerotic aneurysms and suggests the need for an increased clinical suspicion of aneurysm as differential diagnosis when assessing patients of young age with compatible clinical presentation in endemic areas (Tables 3 and 4 ).…”
Section: Investigation Outcomesmentioning
confidence: 99%